(untitled) (La U Investiga, 2021)
The elderly is considered a vulnerable group within the Constitution of the Republic of Ecuador, so it requires specialized care to ensure their quality of life, however, when the Covid-19 pandemic occurred worldwide, all people were forced to social isolation, this situation affected the emotional health of older adults, for this reason this research aims to analyze the presence of depression in older adults by COVID-19 during the health emergency, through a systematic review. Among the findings obtained was that of depression, being the moderate level the one with the highest incidence, with 31%; on the other hand, among the generating factors, fear of contracting the disease and isolation were the most significant. Among the clinical characteristics that prevailed were difficulty sleeping, sadness, and decreased appetite with p values below 0.05. These findings allow us to conclude that depression is a disorder that has been latent in older adults during the pandemic period, affecting their quality of life. Key words: Elderly, Depression, Covid-19, Confinement, Social isolation.